2012
DOI: 10.1037/a0024884
|View full text |Cite
|
Sign up to set email alerts
|

Semantic processing in the production of numerals across notations.

Abstract: In the present work, we conducted a series of experiments to explore the processing stages required to name numerals presented in different notations. To this end, we used the semantic blocking paradigm previously used in psycholinguist studies. We found a facilitative effect of the semantic blocked context relative to the mixed context for Arabic digits and number words. However, the blocked context produced an interference effect for physical numerosity and Roman numbers. Our results provided further evidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
11
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 52 publications
6
11
0
Order By: Relevance
“…The interference effect obtained by Herrera and Macizo (, ) with pictures in the semantic blocking paradigm replicated previous results found with the blocked context paradigm (Damian et al ., ; Kroll & Stewart, ). This interference effect is explained in terms of a competition pattern triggered at the lexical level, due to the semantic processing of stimuli (e.g., Damian et al ., ; although see Navarrete, Del Prato, Peressotti, & Mahon, ; Oppenheim, Dell, & Schwartz, ; for alternative explanations).…”
Section: Introductionsupporting
confidence: 88%
See 1 more Smart Citation
“…The interference effect obtained by Herrera and Macizo (, ) with pictures in the semantic blocking paradigm replicated previous results found with the blocked context paradigm (Damian et al ., ; Kroll & Stewart, ). This interference effect is explained in terms of a competition pattern triggered at the lexical level, due to the semantic processing of stimuli (e.g., Damian et al ., ; although see Navarrete, Del Prato, Peressotti, & Mahon, ; Oppenheim, Dell, & Schwartz, ; for alternative explanations).…”
Section: Introductionsupporting
confidence: 88%
“…Therefore, there are several studies suggesting that Arabic digits are processed semantically. However, there is also recent evidence that runs counter to the notion of semantic mediation in Arabic digit naming (Herrera & Macizo, , ). In these studies, the authors adopted a well‐known paradigm to determine the semantic processing of Arabic numbers: the semantic blocking paradigm (e.g., Damian et al ., ; Kroll & Stewart, ).…”
Section: Introductionmentioning
confidence: 92%
“…In this study, we explored whether semantic processing is required when people say aloud the monetary value of banknotes. Previous work (Macizo & Herrera, ) demonstrated that Euro banknotes can be named without semantic mediation by a direct lexical route similar to that used to name words (Damian et al ., ; Glaser, ) and digits (Herrera & Macizo, , ). The current study shows again that Euro banknotes can be named bypassing the semantic system.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the authors asked whether the processing of banknotes required the accessing to semantic information. To this end, they adopted the blocking paradigm (Damian, Vigliocco, & Levelt, ; Kroll & Stewart, ; Levelt, ) to evaluate the semantic processing of two dimensions that define banknotes: the processing of pictures (Glaser, ) and the processing of numbers (Herrera & Macizo, , ; Roelofs, ). In this paradigm, participants name sequences of pictures in two situations: mixed and blocked.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation